N-Alkynyl Pyrrole Based Total Synthesis of Shensongine A - Reinus, Brandon J.; Kerwin, Sean M. (Synthesis, 2019)
A copper-catalyzed N-alkynylation of pyrrole and a gold-catalyzed spiroketalization were key steps in the total synthesis of the pyrrole spiroketal alkaloid shensongine A. The preparation of this alkaloid is concise and amenable to the rapid synthesis of a diverse library of compounds.
Keywords: cross-coupling; alkynes; nitrogen heterocycles; spiroketalization; shensongine A; pyrrole spiroketal alkaloids; total synthesis